2017
DOI: 10.17533/udea.ikala.v22n03a07
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Implementing a Virtual Learning Environment (VLE) in the EFL Classroom

Abstract: This descriptive qualitative research study aims to identify the impact of implementing a virtual learning environment (VLE) in English as a foreign language (EFL) courses at a public university in Colombia. About 210 students and 5 teachers composed the sample of convenience for this study. As for the research instruments, questionnaires, class observation notes, quick surveys, and teacher narratives were used to gather information related to students' perceptions and attitudes towards the use of this technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 9 publications
2
16
0
3
Order By: Relevance
“…It has an effective impact on increasing the achievement related to cognitive skills of instructional infographic. The result of the current study is consistent with the results concluded by Cappiccie and Desrosiers, 2011, Falloon, 2012, Karabulut and Correia, 2008, Mosquera, 2017, Scharf, 2015, Teo, McNamara, Romeo, and Gronn, 2015, and Wang, Jaeger, Liu, Guo, and Xie, 2013. E-learning effectiveness depends generally on the degree of interaction between the learners and teacher, learners' adherence and self- guidance level.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has an effective impact on increasing the achievement related to cognitive skills of instructional infographic. The result of the current study is consistent with the results concluded by Cappiccie and Desrosiers, 2011, Falloon, 2012, Karabulut and Correia, 2008, Mosquera, 2017, Scharf, 2015, Teo, McNamara, Romeo, and Gronn, 2015, and Wang, Jaeger, Liu, Guo, and Xie, 2013. E-learning effectiveness depends generally on the degree of interaction between the learners and teacher, learners' adherence and self- guidance level.…”
Section: Discussionsupporting
confidence: 91%
“…It also included technological features contributed to increasing the value of student-directed learning and immersion in the virtual environment. many studies have examined the impact of these environments from the perspective of students concluding that students have positive attitudes and increasing enthusiasm and motivation towards the use of these environments in all educational courses (Alves, Miranda, & Morais, 2017;Mosquera, 2017;Omar & Geer, 2018). The success of e-learning environments is highly dependent on a set of elements, including: the quality of the training course design, the educational situation, the learning process organization, and the selection of the e-learning tools, methods and templates that suit the nature of the educational situation, the scientific content and students' needs and characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Video chatting may be especially valuable for EFL learning environments; it has been found to increase L2 production and also foster more sophisticated output (Chun, 1994, Kern, 1995, Kern et al, 2004. In general, students seem to perceive virtual classrooms for EFL learning positively and report good experiences using the platforms (Herrera, 2017).…”
Section: Virtual Classes In Efl Learningmentioning
confidence: 99%
“…VLE, usually applied in schools or higher institutions has been known as an effective medium to enhance the quality of teaching and learning. Furthermore, the development of sophisticated inventions of ICT tools including VLE has shifted the nature of teaching and learning (Barker & Gossman, 2013;Mosquera, 2017). Nowadays, the new kind of pedagogy strategies such as blended learning and on-line learning has become common with the aid of VLE.…”
Section: Introductionmentioning
confidence: 99%